The Use (or rather the non-Use) of Cost-Effectiveness Data in Priority Setting Decisions - Are We Underestimating the Barriers to Using Health Economics in Real World Priority Setting Decisions?; Comment on "Use of Cost-Effectiveness Data in Priority Setting Decisions: Experiences from the National Guidelines for Heart Diseases in Sweden" - Sandra T. Erntoft (Kerman University of Medical Sciences, 2015)
After having practicing and researching health economics for nearly 15 years now, it has become clear to me that the use of cost-effectiveness data in priority setting decisions is rather a rare than a common practice. The Eckard et al.article though, describes a wonderful exception to this rule and a very good example of how it can be used when the conditions are right. However, do we fully understand what these conditions are? In this commentary article I will address some of the institutional and cultural conditions that need to be fulfilled in order for cost-effectiveness data to actually be used in priority setting decisions.